Control wafer bow of InGaP on 200 mm Si by strain engineering. (8th November 2017) - Wang, Bing; Bao, Shuyu; Made, Riko I; Lee, Kwang Hong; Wang, Cong; Lee, Kenneth Eng Kian; Fitzgerald, Eugene A; Michel, Jurgen
Abstract: When epitaxially growing III–V compound semiconductors on Si substrates the mismatch of coefficients of thermal expansion (CTEs) between III–V and Si causes stress and wafer bow. The wafer bow is deleterious for some wafer-scale processing especially when the wafer size is large. Strain engineering was applied in the epitaxy of InGaP films on 200 mm silicon wafers having high quality germanium buffers. By applying compressive strain in the InGaP films to compensate the tensile strain induced by CTE mismatch, wafer bow was decreased from about 100 μ m to less than 50 μ m. X-ray diffraction studies show a clear trend between the decrease of wafer bow and the compensation of CTE mismatch induced tensile strain in the InGaP layers. In addition, the anisotropic strain relaxation in InGaP films resulted in anisotropic wafer bow along two perpendicular (110) directions. Etch pit density and plane-view transmission electron microscopy characterizations indicate that threading dislocation densities did not change significantly due to the lattice-mismatch applied in the InGaP films. This study shows that strain engineering is an effective method to control wafer bow when growing III–V semiconductors on large size Si substrates.